Nicotine increases colon cancer cell migration and invasion through epithelial to mesenchymal transition (EMT): COX‐2 involvement. Issue 6 (15th January 2018) - Dinicola, Simona; Masiello, Maria G.; Proietti, Sara; Coluccia, Pierpaolo; Fabrizi, Gianmarco; Catizone, Angela; Ricci, Giulia; de Toma, Giorgio; Bizzarri, Mariano; Cucina, Alessandra
Abstract : Cigarette smoking is a recognized risk factor for colon cancer and nicotine, the principal active component of tobacco, plays a pivotal role in increasing colon cancer cell growth and survival. The aim of this study was to determine the effect of nicotine on cellular Caco‐2 and HCT‐8 migration and invasion, focusing on epithelial to mesenchymal transition (EMT) induction, and COX‐2 pathway involvement. In both these cell lines, treatment with nicotine increased COX‐2 expression and the release of its enzymatic product PGE2 . Moreover, nicotine‐stimulated cells showed increased migratory and invasive behavior, mesenchymal markers up‐regulation and epithelial markers down‐regulation, nuclear translocation of the β‐catenin, increase of MMP‐2 and MMP‐9 activity, and enhanced NF‐κB expression. Noticeably, all these effects are largely mediated by COX‐2 activity, as simultaneous treatment of both cell lines with nicotine and NS‐398, a selective COX‐2 inhibitor, greatly reduced the number of migrating and invading cells and reverted nicotine‐induced EMT. These findings emphasize that nicotine triggers EMT, leading hence to increased migration and invasiveness of colon cancer cells. Thereby, the use of COX‐2 inhibitor drugs might likely counteract nicotine‐mediated EMT effects on colon cancer development and progression. Abstract : Nicotine induces increased migration and invasion, mesenchymal markers up‐regulation, and epithelial markers down‐regulation in Caco‐2 and HCT‐8 colon cancer cell lines. All these effects are mostly mediated by COX‐2 activity, as simultaneous treatment of both cell lines with nicotine and NS‐398, a selective COX‐2 inhibitor, greatly reduced the number of migrating and invading cells and reverted nicotine‐induced EMT.